The Correlation Between Students' Simple Past Tense and Writing Recount Text Mastery - Sahbila Sahbila; Fitriadi Lubis; Sri Rahmadhani Siregar (English Education : English Journal for Teaching and Learning, 2026)
This study aims to determine the use of the simple past tense and mastery of writing recount texts, as well as to determine the relationship between mastery of the simple past tense and mastery of writing recount texts. This study is a correlational study with a population of eighth-grade students from SMP N 2 Padangsidimpuan. The research sample consisted of 23 students. The researcher used multiple-choice tests for the simple past tense and essay tests for writing recount texts as data collection instruments. The research results indicate a significant relationship between mastery of the simple past tense and mastery of writing recount texts among eighth-grade students at SMP N 2 Padangsidimpuan, with a high correlation.